Which expression is equivalent to 9x − 2x + 3 and why? (1 point) 9x + x, because 9x − (2x − 3) = 9x + x 14x, because 9x −

Question

Which expression is equivalent to 9x − 2x + 3 and why? (1 point)

9x + x, because 9x − (2x − 3) = 9x + x
14x, because 9x − 2x + 3 = 9x + 5x = 14x
10x, because 9x − 2x + 3 = 7x + 3 = 10x
3 + 7x, because (9x − 2x) + 3 = 7x + 3 = 3 + 7x

in progress 0
Skylar 2 weeks 2021-09-11T00:26:43+00:00 1 Answer 0

Answers ( )

    0
    2021-09-11T00:27:44+00:00

    Answer:

    Option D, 3 + 7x

    Step-by-step explanation:

    Step 1:  Combine Like Terms

    9x – 2x + 3

    (9x – 2x) + 3

    7x + 3

    Answer:  Option D, 3 + 7x

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )